MULTILINGUAL INTERACTION IN THE EFL CLASSROOM AT SMA NEGERI 4 TAKALAR - Sitti Wahyuni Saing; Chairil Anwar Korompot; Sukardi Weda (JTechLP: Journal of Technology in Language Pedagogy, 2022)
These studies turned into carried out to determine multilingual interaction in the multilingual EFL classroom between students and teachers. The purpose of this takes a look at was to decide the multilingual interaction and perception of EFL teachers on students' multilingual interactions in EFL. This research used a descriptive qualitative. The subjects were six students and one English teacher in setting SMAN 4 Takalar. Researchers used classroom observations and interviews as research instruments. This reveals and illustrates that multilingual interaction in students' EFL classes is very rarely used because in general students mostly use the Makassarese compared to combining Indonesian with English. That the interaction in the classroom is, classified into categories, namely the teacher-student interaction, the teacher-student interaction (i) the student-teacher interaction, and the student-student interaction. Several students’ interviews also found that some students use social media as a method of mastering their language so that they are not rigid in terms of interaction even by using multiple languages at once. Meanwhile, the teacher's perception that stands out about the interactions carried out by students is the lack of vocabulary they use, so that the teacher can distinguish which students have high and weak levels of multilingual interactions in the classroom